Mergers and acquisitions in EU and Turkey - Civir, Mehtap (My University, 2002)
Bu çalışmanın tem amacı Avrupa Birliği ve Türkiye Rekabet Hukukları kapsamında birleşmeler ve devralmaların kontrolünü karşılıklı olarak incelemektir. Globalleşmenin bu denli önem kazandığı günümüzde, işletmeler gerek uluslararası piyasada gerekse iç piyasada gelişen rekabet ortamında varlıklarını sürdürebilmek ve kar marjını yükseltmek için birleşme veya devralma yolunu seçmektedirler. Birleşmeler ve devralmalar pazardaki rekabeti artırmakta ise de çoğu zaman birleşen veya devralan şirketin pazarda hakim duruma geçmesi ile rekabeti kısıtlamakta hatta sona erdirmektedir. Bu sebeple, birleşmeler ve devralmalar Rekabet Hukuku kapsamında, rekabetin korunması amacıyla, kontrol edilmekte ve gerekirse izin verilmemektedir. Avrupa Birliği'nde Roma Antlaşması 81 ve 82. md. (eski 85 ve 86. md.) Avrupa Birliği üye ülkelerinde ulusal bazda ve birlik çapında rekabeti koruyan ana kuralları düzenlemiştir. Roma Antlaşmasının anılan maddeleri ışığında 4064/ 89 sayılı birleşemelr ve devralmalar hakkında ki tüzük düzenlenmiştir. Bu tüzük Avrupa Birliği'nde birleşemelr ve devralmaların kontrolü hakkında kuralları düzenlemektedir. Tür hukukunda ise 4054 sayılı Rekabet Kanunu 7. md. Birleşemler ve devralmaları tarif etmekte ve hangi tür birleşmelerin izne tabi olduğunu düzenlemektedir. Reakabet Kanunun md. 7 ışığında 1997/ 1 sayılı Birleşmeler ve Devralmalar Hakkında Tebliğ ise Reakabet Hukukuna göre hangi tür birleşmelere izin verileceği ve hangilerinin yasaklandığını açıkça düzenlemiştir. The essential objective of this work is the comparative study of the mergers and acquisitions control in respect to European Community Law of Competition and Turkish Law of Competition. In our time, when Globalization earned a substantial significance, the companies are choosing to merge or acquire with other companies in return to survive and exist in the local and/ or international competition markets, increase their profit margins or get stronger in a competitive environment. Although mergers and acquisition occasionally increase the level of competition, most of the time, the competition is restricted or sometimes completely destroyed when the merging or acquiring company assumes a dominant position in the market. Thus, for the protection of the competition in the market, the control of mergers and acquisitions both in local and international markets is rather significant. The articles 81 and 82 ( formerly 85 and 86) of the Rome Treaty that incorporated European Community, defines the rules of competition with an objective of maintaining the free trade of commodities and services amongst the nations and forming an intensive competition environment . These articles are also the foundations of the Regulation Nr. 4064/ 89 that controls mergers and acquisitions. European Economical Community Merger Control Regulation 4064/ 89 regulates the control of mergers and acquisitions. In Turkish Law, Act Nr. 4054 On the Protection of Competition Article 7 defines the mergers and acquisitions and specified the types of mergers and acquisitions prohibited by the Law. Additionally, according to clause 2 of the same article, Notification On the Mergers and Acquisitions Subjected to Permission from the Commission of Competition Nr.1997/ 1 regulates as to which types of mergers and acquisitions are subjected to permission from the Commission of Competition.
Keywords: Avrupa Birliği